Video Game dan Iman Katolik: Studi Kualitatif ‘That Dragon, Cancer’ pada Kalangan Misdinar di Kota Batam - Wibowo, Tony; Saribu, Aloysius Edward Marselino Dolok (Serat Rupa: Journal of Design, 2023)
Video games are a means of entertainment especially among children and adolescent, including acolyte. Several video games use narration as dialogue to convey the story in video games. One of the video games that heavily focused on narrative is the video game That Dragon, Cancer. This video game tells of a family who has a child who has brain cancer. In that video game, it shows struggle of each family member deal with it in a surreal and enigmatic visual presentation. This study aims to prove is it possible to have positive view on Cotholic faith among acolytes by playing the video game That Dragon, Cancer. This study involved 30-acolyte which all of them play the video game without context and then we interviewed them. We found that the video game That Dragon, Cancer could create positive views of Catholic faith through narratives and video game design that show us to accept death and belief in God.